2014
DOI: 10.1158/1535-7163.mct-13-0753
|View full text |Cite
|
Sign up to set email alerts
|

Differential Antitumor Activity of Aflibercept and Bevacizumab in Patient-Derived Xenograft Models of Colorectal Cancer

Abstract: The recombinant fusion protein aflibercept (ziv-aflibercept in the United States) binds VEGF-A, VEGF-B, and placental growth factor (PlGF). The monoclonal antibody bevacizumab binds VEGF-A. Recent studies hypothesized that dual targeting of VEGF/PlGF is more beneficial than targeting either ligand. We compared activity of aflibercept versus bevacizumab in 48 patient-derived xenograft (PDX) colorectal cancer models. Nude mice engrafted subcutaneously with PDX colorectal cancer tumors received biweekly afliberce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 46 publications
3
28
0
1
Order By: Relevance
“…However, there is available data from pre-clinical studies that have made a comparative assessment of the activity of the two drugs. A recent study with mCRC tumour tissue models extracted from patients and xenografted mice (PDX cancer models) revealed differences in tumour growth control between the antiangiogenic treatments bevacizumab and aflibercept; the latter was revealed to be more effective in preventing tumour growth (25). Chiron et al (26) verified this data, also using PDX models, and revealed that administrating aflibercept during cancer progression following bevacizumab treatment facilitates maintenance of tumour growth inhibition, thus achieving a greater response compared with bevacizumab maintenance following tumour progression (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is available data from pre-clinical studies that have made a comparative assessment of the activity of the two drugs. A recent study with mCRC tumour tissue models extracted from patients and xenografted mice (PDX cancer models) revealed differences in tumour growth control between the antiangiogenic treatments bevacizumab and aflibercept; the latter was revealed to be more effective in preventing tumour growth (25). Chiron et al (26) verified this data, also using PDX models, and revealed that administrating aflibercept during cancer progression following bevacizumab treatment facilitates maintenance of tumour growth inhibition, thus achieving a greater response compared with bevacizumab maintenance following tumour progression (26).…”
Section: Discussionmentioning
confidence: 99%
“…This superior activity may be explained by the effect aflibercept has on VEGF and PIGF, since it better neutralises the resistance mechanisms that are activated by the tumour compared with bevacizumab (27,28). In addition, it has been suggested that PIGF presence in patient serum may aid in the prediction of the optimal time for switching to antiangiogenic therapy prior to tumour progression taking place (25). …”
Section: Discussionmentioning
confidence: 99%
“…Aflibercept appears to have greater anti-VEGF [10] and antitumor [20] activity than bevacizumab. The binding affinity of aflibercept to human VEGF-A 165 isoform was &118-fold higher than that of bevacizumab [10].…”
Section: Preclinical Studiesmentioning
confidence: 94%
“…Furthermore, aflibercept blocked human PIGF-2 induced VEGFR-1 activation and HUVEC migration, whereas bevacizumab does not bind to P1GF-2 and therefore showed no such activity [10]. In mice bearing human colorectal cancer xenografts, aflibercept induced complete tumour stasis in 31 of 48 animals, whereas bevacizumab in 2 of 48; aflibercept also significantly (p \ 0.05) inhibited tumour growth versus bevacizumab in 39 of 48 animals, including in nine animals in which bevacizumab was inactive [20]. In this model, aflibercept down-regulated a number of angiogenesis-promoting genes and that may be associated with its increased antitumour activity relative to bevacizumab [21].…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…Молекула афли-берцепта обладает большей связующей способностью в сравнении с бевацизумабом в отношении VEGFA [5][6][7][8][9][10][11].…”
Section: механизм действия эффективность токсичностьunclassified